Potential of macronutrients and probiotics to boost immunity in patients with SARS-COV-2: a narrative review - Mardi, Afrouz; Kamran, Aziz; Pourfarzi, Farhad; Zare, Maryam; Hajipour, Azadeh; Doaei, Saeid; Abediasl, Negin; Hackett, Daniel (Frontiers in Nutrition, 2023)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2) may cause inflammation and increased cytokine secretion. Dietary factors may play an important role in enhancing the immune responses against infectious diseases such as SARS-COV-2. This narrative review aims to determine the effectiveness of macronutrients and probiotics to improve immunity in SARS-COV-2 patients. Dietary proteins may boost pulmonary function in SARS-COV-2 patients through inhibitory effects on the Angiotensin-converting enzyme (ACE) and reduce Angiotensin (ANG-II). Moreover, omega-3 fatty acids may improve oxygenation, acidosis, and renal function. Dietary fiber may also produce anti-inflammatory effects by reducing the level of high-sensitivity C-Reactive Protein (hs-CRP), Interleukin (IL-6), and Tumor necrosis factor (TNF-α). In addition, some evidence indicates that probiotics significantly improve oxygen saturation which may enhance survival rate. In conclusion, the consumption of a healthy diet including adequate macronutrients and probiotic intake may decrease inflammation and oxidative stress. Following this dietary practice is likely to strengthen the immune system and have beneficial effects against SARS-COV-2.